2019
DOI: 10.1093/bib/bbz130
|View full text |Cite
|
Sign up to set email alerts
|

An extensive review of tools for manual annotation of documents

Abstract: Motivation Annotation tools are applied to build training and test corpora, which are essential for the development and evaluation of new natural language processing algorithms. Further, annotation tools are also used to extract new information for a particular use case. However, owing to the high number of existing annotation tools, finding the one that best fits particular needs is a demanding task that requires searching the scientific literature followed by installing and trying various t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
79
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 56 publications
0
79
0
1
Order By: Relevance
“…An extensive analysis and comparison of several annotation tools is provided in Neves and Ŝeva [18]. Table 2 summarizes the main characteristics we considered relevant for this research and identifies the most appropriate annotation tool among a subset of popular alternatives.…”
Section: Technologies For Annotation and Resource Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive analysis and comparison of several annotation tools is provided in Neves and Ŝeva [18]. Table 2 summarizes the main characteristics we considered relevant for this research and identifies the most appropriate annotation tool among a subset of popular alternatives.…”
Section: Technologies For Annotation and Resource Distributionmentioning
confidence: 99%
“…Qualitative comparison of popular annotation tools. Adapted fromTable 3in Neves and Ŝeva[18],Table 3. A symbol ≈ indicates that the corresponding feature is only partially supported.…”
mentioning
confidence: 99%
“…Prior to the publication of an extensive review of 78 annotation tools by Neve and Seva [12], we started a review of annotation tools for Twitter data. The inclusion criteria for our review were the availability and the ease of installation of the tools, or otherwise, a demonstration of the tool online.…”
Section: Adapting Existing Annotation Tools For Twittermentioning
confidence: 99%
“…Many annotation tools have been developed for manual tagging of entities within a document for the biological domain and other domains. A detailed recent review of the strengths and weaknesses of different methods can be found in Neves and Seva's study [4]. To gauge the support for non-contiguous entities, we manually tested the 15 tools selected in that review with an overview shown in Table 2.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the annotation tools reviewed in Neves and Seva's study[4] for their capabilities to annotate non-contiguous entities…”
mentioning
confidence: 99%